The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-23364-9
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Statin Therapy based on ACC/AHA and NCEP ATP-III Guidelines: An Iranian Survey of Non-Communicable Diseases Risk Factors

Abstract: To compare the burden of statin therapy according to the Third Adult Treatment Panel (ATP-III) and the American College of Cardiology/American Heart Association (ACC/AHA) guidelines the Survey of Risk Factors of Non-Communicable Disease (SuRFNCD)−2011of Iran was used. A survey analysis associated with sex and age categorization was run. Of total 3496 persons (1322 men) aged 40–70 years, based on the ACC/AHA guidelines, about 46.5% were eligible to receive moderate- to high-intensity statin therapy. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
3
1
1
Order By: Relevance
“…However in a longitudinal study in the country with a 10-year follow-up of people aged 40-75 years, a high incidence of CVD (21.0% in men and 12.0% in women) was reported (20). Another study found that 46.5% of Iranians were eligible for statin therapy according to the ACC/AHA guideline (21). Our prevalence of high CVD risk (28.3%) is slightly higher than recent research in Malaysia (20.5%) (22), Australia (19.9%) (23) and the United States of America (22.6% in hypertensive patients) (24).…”
Section: Discussioncontrasting
confidence: 50%
“…However in a longitudinal study in the country with a 10-year follow-up of people aged 40-75 years, a high incidence of CVD (21.0% in men and 12.0% in women) was reported (20). Another study found that 46.5% of Iranians were eligible for statin therapy according to the ACC/AHA guideline (21). Our prevalence of high CVD risk (28.3%) is slightly higher than recent research in Malaysia (20.5%) (22), Australia (19.9%) (23) and the United States of America (22.6% in hypertensive patients) (24).…”
Section: Discussioncontrasting
confidence: 50%
“… 9 One possible reason behind this achievement is the high use of statins among the Iranian population. 25 While self-reported use of oral anti-diabetes medications was comparable between the two databases (68.7% in STEPS 2016 and 68.4% in 2013–2014 NHANES), Iranian patients with diabetes reported the use of insulin significantly less than their American counterparts (15.7% vs. 28.6%). 9 Anti-diabetes medications, including insulin, are widely available for use in the country.…”
Section: Discussionmentioning
confidence: 88%
“…This decrease could be mainly attributed to statin prescription and dietary modifications, e.g., replacement of saturated with unsaturated fats and reduction in trans-fats. In a recent study on non-communicable disease in Iran, approximately half (46.5%) of 40–70-year Iranians were eligible for moderate- to high-intensity statin therapy based on American College of Cardiology and the American Heart Association (ACC/AHA) guideline [ 32 ]. Serum HDL-C levels, however, changed only modestly.…”
Section: Discussionmentioning
confidence: 99%